Аналіз структурних змін в економіці: методика дослідження - Пелех, Оксана Богданівна; Юськів, Богдан Миколайович; Pelekh, Oksana B.; Yuskiv, Bohdan M. (Інститут підготовки кадрів державної служби зайнятості України, 2019)
Базовою умовою сучасного економічного розвитку і зростання є постійні структурні зміни в рамках економічної системи, завдяки чому система намагається адекватно реагувати на зміни середовища свого існування. Важливим завданням макроекономічного аналізу стає виявлення та аналіз структурних змін. У роботі представлено методику аналізу структурних змін в економіці. Методика передбачає проведення аналізу на двох рівнях – аналіз процесу структурних змін і аналіз змін структури. Перший рівень стосується характеристик самого процесу змін, тоді як другий дозволяє відповісти на запитання, як змінюється досліджувана структура. Аналіз процесу структурних змін базується на визначенні й аналізі трьох оцінок: інтенсивність змін; швидкість змін; сталість змін. Другий рівень аналізу передбачає декомпозицію структурних змін на рівень елементів структури й аналіз на цій підставі змін розміру (зміни величини елемента / елементів) і змін форми структури (зміни пропорцій між елементам і цілим).

One of the basic requirements for the economic growth and development are constant structural changes of the economic system, enabling the latter to adequately respond to its environment changes. The main task of the macroeconomic analysis is to define and analyze structural changes. The article deals with methods of economy’s structural changes analysis. The employed methodology approach envisions economic development outline within three aspects: quantitative (extensive development), structural and qualitative (intensive development). Structure is an aggregate one one-dimensional objects creating an integrity. Each object is a separate system structural characteristic, whereas their wholeness describes the system itself. In terms if structure these characteristics are interconnected: changes in ones creates changes in others, and this influence is different with different characteristics/their sets. The proposed analysis method of structural changes is called “two-dimensional quantitative analysis of local structural matrix”. Multidimensional and multilevel economic system is an aggregate of sub-systems, each of which describes separate logical entity and possesses its own structure. Therefore, study of the systems has to be based upon studying the local aggregate structures, and study of the system’s structural changes dynamics are to be based upon analysis of structural changes in local structures. To study each local structure, a separate structural matrix is built. Matrix enables to separate those exact elements, formed to enable the needed common interaction, as well as accents the principal impossibility to change one object without changing the rest system structural elements. The method envisions two-dimensional analysis – the structural changes process analysis and the structural changes analysis. The first dimension deals with characteristics of the changes process itself, whereas the second one allows to answer the question of how exactly the studied structure changes. The structural changes process analysis is based upon defining and further analysis of the three markers: changes intensity; changes speed; changes sustainability. The second analysis dimension envisions decomposition of structural changes to the level of structural elements, as well as the corresponding analysis of the change measures (element(s) size changes) and the structure shape changes (proportion changes between the elements and the aggregate).
Structural economy changes analysis: methods and methodology of study
Keywords: національна економіка; структура економіки; структурні зміни; аналіз структурних змін; методологія і методика аналізу; national economy; economy structure; structural changes; structural changes analysis; analysis methods and methodology